Association of HOTAIR rs1899663 G>T Polymorphism with Colorectal Cancer in the Turkish Population: A Case–Control Study - Yalınbaş Kaya, Berrin; Peker, Betül; Tuğrul, Fuzuli; Alkan Tali, Özge; Bayram, Süleyman (Turkish Journal of Gastroenterology, 2022)
Background: Long noncoding RNAs increase the overexpression of oncogenes. Cancer development and metastasis of cancer may occur as a result of overexpression of oncogenes. Polymorphisms in the genes (such as HOTAIR, etc.) in which long noncoding RNAs are synthesized affect the expression of these genes. Therefore, these polymorphisms may play a role in cancer development and cancer metastasis. The present study aimed to evaluate the association between HOTAIR gene rs1899663 G>T polymorphism with colorectal cancer. Methods: The current study examined the HOTAIR gene rs1899663 G>T polymorphism in 100 patients with colorectal cancer and 93 healthy persons by a real-time polymerase chain reaction. Results: The G and T allele frequencies of the HOTAIR rs1899663 polymorphism were significantly different between the case and control groups (P = .01). The persons carrying the G allele had a protective effect against colorectal cancer, while individuals carrying the T allele were predisposed to colorectal cancer (P = .001). Four of 5 colorectal cancer recurrence patients had the TT genotype (P = .02). Conclusion: This research is the first to demonstrate the relationship between colorectal cancer and the HOTAIR gene rs1899663 polymorphism in the Turkish population, which is a Caucasian population. Our results suggest that the rs1899663 G allele has a protective role for colorectal cancer in the Turkish population. However, it would be appropriate to conduct this research with a larger sample to confirm this result in the Turkish population Cite this article as: Yalınbaş Kaya B, Peker B, Tuğrul F, Alkan Tali Ö, Bayram S. Association of HOTAIR rs1899663 G>T polymorphism with colorectal cancer in the Turkish population: A case–control study. Turk J Gastroenterol. 2022;33(8):689-695.